THE INFLUENCE OF COMPETENCY ON EMPLOYEE PERFORMANCE THROUGH TALENT MANAGEMENT AT PT. BARUGA ASRINUSA DEVELOPMENT - Ismail; Nurdjanah Hamid; Abdul Razak Munir (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2023)
One of the most fundamental problems in the process of improving employee performance in a company is employee competence which is influenced by talent management. This study aims to determine and justify the influence of competence on employee performance through talent management in PT. Baruga Asrinusa Development. The method in this study uses quantitative methods using the path analysis method (path analysis) to measure the influence of competence on employee performance through talent management. The results of this study show that competence has a positive and significant effect on talent management, competence has a positive and significant effect on employee performance, talent management has a positive and significant effect on employee performance and competence has a positive and significant effect on employee performance through talent management.